2006
DOI: 10.1088/0965-0393/14/2/001
|View full text |Cite
|
Sign up to set email alerts
|

The influence of phase transformations on residual stresses induced by the welding process—3D and 2D numerical models

Abstract: In this work, a numerical study of laser beam welding of steel was performed. In particular, phase transformation effects were considered, which consist mainly of volume change and transformation plasticity. Thanks to the possibilities of numerical modelling, additional analyses were performed (a) without taking into account phase transformations and (b) considering only the transformation plasticity phenomenon.The aim of this study was to examine the influence of phase transformation on the residual stress in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(52 citation statements)
references
References 30 publications
2
45
0
Order By: Relevance
“…The thermal conductivity is artificially increased for the compensation of convection stirring effect in the molten pool (Lindgren, 2001). Furthermore, the latent heat of phase change is considered by modifying the specific heat curve with the change of temperature (Ferro et al, 2006).…”
Section: Finite Element Modelmentioning
confidence: 99%
“…The thermal conductivity is artificially increased for the compensation of convection stirring effect in the molten pool (Lindgren, 2001). Furthermore, the latent heat of phase change is considered by modifying the specific heat curve with the change of temperature (Ferro et al, 2006).…”
Section: Finite Element Modelmentioning
confidence: 99%
“…5(a), exhibit essentially the same residual stress level at the weld centerline, but while approaching the fusion line there is a discrepancy between a constant level for the case neglecting large deformations and the decreasing residual stress level for the case of large deformations. The behavior represented by the large deformations calculation does not correspond to usual residual stress evolution in plain carbon steels [6,[33][34][35]. A higher stress level in the weld would assume a strain hardening effect that is larger in the weld than in the HAZ.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the on-cooling phase transformation behavior has been integrated in finite element simulations of steel [4][5][6][7][8]. These studies have all shown the strong effect of the austenite to martensite transformation on the final residual stress state.…”
Section: Introductionmentioning
confidence: 99%
“…During solidification and cooling of a multi-phase material, the variation of the specific volume and the 'transformation plasticity' [22] associated to phase transformation, influence the thermal and residual stresses induced by thermal loads. It was shown that such effects are so high that any numerical model of welding process that doesn't take into account phase transformation effects fails in calculating the thermal and residual stress filed [26]. When the scale of observation is focused on about one tenth of the notch depth, it was observed that phase transformation changes the sign of residual stresses if compared to the results obtained in a simplified mono-phase material [20].…”
Section: Influence Of Phase Transformation On Residual Stress Fieldmentioning
confidence: 99%